Diaphragm composite material and preparation method thereof

By using a composite structure of PEN film layer, aluminum-coated film layer, aerogel layer and elastic adhesive layer in the diaphragm material, the shortcomings of the existing diaphragm materials in noise reduction, damping performance and electromagnetic shielding performance are solved, and a diaphragm composite material with high strength, good shock absorption and noise reduction and heat resistance are achieved.

CN111267411BActive Publication Date: 2025-04-08ZHEJIANG PENGYUAN NEW MATERIAL TECH GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202010189623.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-03-18
Publication Date
2025-04-08
Estimated Expiration
2040-03-18

AI Technical Summary

Technical Problem

Existing diaphragm materials perform poorly in noise reduction, damping performance and electromagnetic shielding performance, and are susceptible to damage or oxidation, resulting in reduced mass and shortened life.

Method used

The composite structure of PEN film layer, aluminum-plated film layer, aerogel layer and elastic adhesive layer is adopted. The PEN film layer increases plasticity and heat resistance, the aluminum-plated film layer improves damping performance and electromagnetic shielding performance, the aerogel layer provides protection effect, and the elastic adhesive layer enhances toughness.

Benefits of technology

The high-strength and good shock and noise reduction effect of the diaphragm composite layer are achieved, the heat resistance and toughness are enhanced, and the electromagnetic shielding performance, wear resistance and corrosion resistance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111267411B_ABST
    Figure CN111267411B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of composite film technology, and in particular to a diaphragm composite material and a preparation method thereof, wherein the diaphragm composite layer structure comprises a PEN film layer, an aluminized film layer, an aerogel layer, and an elastic adhesive layer disposed between the PEN film layer and the aluminized film layer for bonding the PEN film layer and the aluminized film layer, and the aerogel layer is coated on a side of the aluminized film layer away from the elastic adhesive layer. The diaphragm composite layer of the present invention has high strength and rigidity, has better vibration reduction and noise reduction, and is wear-resistant and corrosion-resistant, and is worthy of popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite membranes, and in particular to a diaphragm composite material and a preparation method thereof. Background Art

[0002] Speakers are an important acoustic component in electronic devices. They are a kind of sound amplification equipment that converts sound wave signals into sound signals and transmits them. Speakers usually include a vibration system and a magnetic circuit system. The vibration system includes a diaphragm and a voice coil combined together. The diaphragm is one of the important components of the speaker and plays a vital role in the sound performance of the speaker. It determines the quality of the speaker's conversion from electrical energy to sound energy.

[0003] The existing diaphragms on the market are usually made of a composite material of ordinary polyurethane (TPU) thermoplastic elastomer, engineering plastics and adhesive film. The performance and effect of this diaphragm are not good: it generates a lot of noise, has weak damping performance and electromagnetic shielding performance, and is prone to interference during operation. With the continuous development of the market demand for acoustic products, users have put forward higher requirements for the acoustic performance and reliability of speakers.

[0004] The utility model patent with announcement number CN206302564U discloses a diaphragm composite layer of a sound-generating device and a sound-generating device, including a metal layer, an aerogel layer and a polyester film layer, wherein the metal layer is used as the top layer of the diaphragm composite layer, the polyester film layer is used as the bottom layer of the diaphragm composite layer, and the aerogel layer is used as an interlayer of the diaphragm composite layer and is arranged between the metal layer and the polyester film layer, and the diaphragm composite layer is configured to be attached to the diaphragm of the sound-generating device. Although the provision of the aerogel layer in this technology reduces the weight of the diaphragm composite layer to a certain extent, since the aerogel layer is provided between the metal layer and the polyester film layer, it cannot provide good protection for the diaphragm composite layer, and its outer surface layer is easily damaged or oxidized, resulting in a decrease in the quality of the diaphragm composite layer and a shortened lifespan.

[0005] The utility model patent with announcement number CN202873041U discloses a composite diaphragm, which is provided with a polyetheretherketone film and a thermoplastic polyurethane elastomer attached to the surface of the polyetheretherketone film. The composite diaphragm of the utility model adds a thermoplastic polyurethane elastomer to the polyetheretherketone film. Although the composite diaphragm has good stability to environmental changes, can effectively reduce the resonant frequency of the product, widen the frequency band, improve the power resistance of the speaker, and has a simple process and low production cost; however, the composite diaphragm formed by the composite between layers has poor damping performance and cannot meet the application of speakers in the low-frequency field.

[0006] Invention patent CN106003668A discloses a method for preparing a silicone diaphragm and a silicone diaphragm, wherein the silicone diaphragm is prepared by continuously introducing a formed silicone film into a mold cavity of a molding machine to keep the silicone film flat in the mold cavity; closing the mold and controlling the mold temperature; adjusting the molding pressure and maintaining the pressure for a period of time; and preparing the required silicone diaphragm. Although the process operation of the silicone diaphragm is simple and the molding is convenient, large-scale preparation can be achieved; however, the silicone diaphragm is only made by closing the silicone film up and down or left and right. Since the silicone diaphragm is made of a single material, the damping performance of the silicone diaphragm is insufficient. When used in a speaker, the low frequency of the speaker is slightly flawed and the low-frequency performance is insufficient. It is difficult to meet people's high-quality requirements for electronic equipment. Summary of the invention

[0007] In order to solve the problems raised in the above background technology, the present invention provides a diaphragm composite material and a preparation method thereof.

[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solutions: a diaphragm composite material, comprising a PEN film layer, an aluminum-plated film layer, an aerogel layer, and an elastic adhesive layer arranged between the PEN film layer and the aluminum-plated film layer for bonding the PEN film layer and the aluminum-plated film layer, wherein the aerogel layer is coated on a side of the aluminum-plated film layer away from the elastic adhesive layer.

[0009] Preferably, the aluminized film layer comprises a PET film and a metal aluminum layer evaporated on the surface of the PET film.

[0010] Preferably, the PEN film layer is mainly made of a mixture of polyester PEN, nylon 6 and fiber-type filler.

[0011] Preferably, the fiber-type filler is one or more of glass fiber, ceramic fiber and carbon fiber.

[0012] Preferably, the elastic adhesive layer is mainly made of polyacrylate elastomer or polyurethane elastomer.

[0013] Preferably, the aerogel layer is mainly prepared from silicon oxide-silicon nitride composite aerogel or silicon dioxide-phenolic resin composite aerogel.

[0014] The present invention also provides a method for preparing the above-mentioned diaphragm composite material, the preparation method comprising the following steps:

[0015] S1: Preparation of PEN film layer, the specific preparation steps include:

[0016] S1.1: Weigh the following materials by weight: 70-80 parts of polyethylene naphthalate, 10-15 parts of nylon 6, 10-15 parts of fiber-type filler, 1-2 parts of silane coupling agent and 0.5-1 part of lubricant; add the weighed materials into a mixer, mix and stir to form a mixture;

[0017] S1.2: Add ethanol to the mixture and stir, then add it to the extruder for melt blending and extrusion granulation; the mass ratio of ethanol to the mixture is 1:(4-6);

[0018] S1.3: drying the extruded particles in step S1.2 and adding them to an injection molding machine for injection molding to obtain a long-chain branched PEN film layer;

[0019] S2: Preparation of aerogel layer material, the specific preparation steps include: adding 20-30 parts of propylene oxide, 80-130 parts of acetic acid, 50-70 parts of polyethylene glycol 600 and 10-30 parts of formamide to a high-speed micro-powder mixer and stirring for 5-10 minutes, and adjusting the solution temperature to 5-8°C, then adding 5-20 parts of silicon oxide-silicon nitride composite aerogel, 20-30 parts of toluene diisocyanate trimer, and 10-15 parts of isophorone diisocyanate trimer, and continuing to stir for 5-10 minutes; then airflow classification, collecting the powder passing through an 8000 mesh filter, which is the aerogel layer material; the speed of the high-speed micro-powder mixer is 800-1000r / min;

[0020] S3: The aerogel layer material powder collected in step S2 is passed through compressed air, filtered, and dried, and then enters a high-temperature gasification chamber of 800-1000°C, and a supersonic airflow is formed through a nozzle and injected into the surface of the aluminum-plated side of the aluminum-plated film layer, and the side surface is continuously irradiated with a high-speed plasma light to form an aluminum-plated film layer with an aerogel layer attached to one side;

[0021] S4: The elastic adhesive is evenly coated on the surface of the PEN film layer, and then laminated and pressed with the surface of the aluminum-coated film layer on which the aerogel layer is not attached. The laminating roller dimension is 60-80°C and the pressure is 120-160MPa. After laminating, it is aged at 35-50°C for 60-75h to obtain a diaphragm composite material.

[0022] Preferably, in step S3, the plasma light speed voltage is 1200-1450 KV, and the irradiation time is 2-5 s.

[0023] Preferably, the specific preparation steps of the silicon oxide-silicon nitride composite aerogel in step S2 include:

[0024] 1) The following materials are mixed by weight: 1 part of TEOS, (2.5-4) parts of anhydrous ethanol and (2.5-4) parts of water are thoroughly stirred and the pH value is adjusted to 4 with dilute hydrochloric acid to form sol A;

[0025] 2) adjusting the pH value of sol A to 7 with ammonia water, adding 1 to 1.5 parts by weight of silicon nitride under stirring, and standing at room temperature to form gel B;

[0026] 3) aging gel B at room temperature for 24 h, then immersing gel B in anhydrous ethanol at room temperature and continuing aging for 48 h;

[0027] 4) The aged gel B was immersed in a hexane solution containing 10% trimethylsilane for 6 hours to perform a hydrophobic treatment;

[0028] 5) Drying the gel B treated in step S2.4 at 80-100° C. under normal pressure; treating the dried gel B in a furnace at 450-500° C. for 4-6 hours, and crushing it to obtain a silicon oxide-silicon nitride composite aerogel.

[0029] Preferably, in step 2), the average particle size of silicon nitride is 30 to 50 nm.

[0030] Preferably, the trimethylsilane in step 4) may also be trimethylchlorosilane, long-chain methylsilane or methylfluorosilane.

[0031] Preferably, the silane coupling agent in step S1 is KH-550, KH-560 or KH-570.

[0032] The beneficial effects of the present invention are: the diaphragm composite layer described in the present invention has high strength and strong rigidity, and has better shock absorption and noise reduction effects; through the setting of the PEN film layer, the plasticity of the diaphragm composite layer can be increased and its heat resistance can be improved; the setting of the elastic adhesive bonds the PEN layer and the aluminum-plated film layer, which greatly increases the toughness of the diaphragm composite layer; and the setting of the aluminum-plated film layer increases the damping performance and electromagnetic shielding performance of the diaphragm composite layer, and at the same time makes it have better heat resistance and higher strength; and the setting of the aerogel can protect the aluminum-plated film layer, making it more wear-resistant and corrosion-resistant. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the overall structure of the diaphragm composite material in the present invention.

[0034] Among them: 1-PEN film layer, 2-elastic adhesive layer, 3-aluminum-plated film layer, 31-PET film, 32-metal aluminum layer, 4-aerogel layer. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with the embodiments.

[0036] A diaphragm composite material, comprising a PEN film layer 1, an aluminized film layer 3, an aerogel layer 4, and an elastic adhesive layer 2 arranged between the PEN film layer and the aluminized film layer 3 for bonding the PEN film layer 1 and the aluminized film layer 3, wherein the elastic adhesive layer 2 is made of a thermoplastic elastomer, specifically mainly made of a polyacrylate elastomer or a polyurethane elastomer, and the thickness of the elastic adhesive layer 2 is 12 to 65 μm. The setting of the elastic adhesive layer 2 can not only well bond the PEN film layer 1 and the aluminized film layer 3, but also make the material have a certain toughness, thereby increasing the durability of the product; the aluminized film layer 3 comprises The PET film 31 and the metal aluminum layer 32 vapor-deposited on the surface of the PET film 31, the setting of the metal aluminum layer 32 improves the damping performance and electromagnetic shielding performance of the diaphragm composite layer, and the setting of the PET film 31 increases the strength of the composite film and has better heat resistance; the PEN film layer 1 provides a base material for the diaphragm composite layer, increases the overall rigidity of the diaphragm composite layer, and improves its heat resistance and plasticity. The aerogel layer 4 is coated on the side of the aluminum-plated film layer 3 away from the elastic adhesive layer 2. The setting of the aerogel layer 4 can protect the aluminum-plated film layer and improve its wear resistance and corrosion resistance.

[0037] In this embodiment, the PEN film layer 1 is mainly made of a mixture of polyester PEN, nylon 6 and fiber-type filler.

[0038] In this embodiment, the fiber-type filler is one or more of glass fiber, ceramic fiber, and carbon fiber.

[0039] In this embodiment, the aerogel layer is mainly prepared from silicon oxide-silicon nitride composite aerogel or silicon dioxide-phenolic resin composite aerogel, so that the diaphragm composite layer has better wear resistance and corrosion resistance, making it more durable.

[0040] A method for preparing the above-mentioned diaphragm composite material, the preparation method comprising the following steps: S1: preparation of a PEN film layer, the specific preparation steps comprising:

[0041] S1.1: Dry the material PEN (i.e. polyethylene naphthalate) at 100-130°C for 2.5-4h; then weigh the following materials by weight: 70-80 parts of PEN, 10-15 parts of nylon 6, 10-15 parts of fiber-type filler, 1-2 parts of silane coupling agent and 0.5-1 part of lubricant; and add the weighed materials into a mixer and mix and stir to form a mixture;

[0042] S1.2: Add ethanol to the mixture and stir, then add it to the extruder for melt blending and extrusion granulation; the mass ratio of ethanol to the mixture is 1:(4-6);

[0043] S1.3: drying the extruded particles in step S1.2 and adding them to an injection molding machine for injection molding to obtain a long-chain branched PEN film layer;

[0044] The silane coupling agent may be KH-550, KH-560 or KH-570;

[0045] Wherein, in step S1.2, the extruder is a twin-screw extruder, the screw speed is 40-60 rpm, and the temperature from the extruder hopper to the die area is 240-260°C;

[0046] In step S1.3, the nozzle temperature of the injection molding machine is 250-270°C, and the injection pressure is 65-75 MPa;

[0047] S2: Preparation of aerogel layer material, the specific preparation steps include: adding 20-30 parts of propylene oxide, 80-130 parts of acetic acid, 50-70 parts of polyethylene glycol 600 and 10-30 parts of formamide to a high-speed micro-powder mixer and stirring for 5-10 minutes, and adjusting the solution temperature to 5-8°C, then adding 5-20 parts of silicon oxide-silicon nitride composite aerogel, 20-30 parts of toluene diisocyanate trimer, and 10-15 parts of isophorone diisocyanate trimer, and continuing to stir for 5-10 minutes; then airflow classification, collecting the powder passing through an 8000 mesh filter, which is the aerogel layer material; the speed of the high-speed micro-powder mixer is 800-1000r / min;

[0048] S3: The aerogel layer material powder collected in step S2 is passed through compressed air, filtered, and dried, and then enters a high-temperature gasification chamber of 800-1000°C, and a supersonic airflow is formed through a nozzle and injected into the surface of the aluminum-plated side of the aluminum-plated film layer, and the side surface is continuously irradiated with a high-speed plasma light to form an aluminum-plated film layer with an aerogel layer attached to one side;

[0049] S4: The elastic adhesive is evenly coated on the surface of the PEN film layer, and then laminated and pressed with the surface of the aluminum-plated film layer on which the aerogel layer is not attached. The laminating roller dimension is 60-80°C and the pressure is 120-160MPa. After laminating, it is aged at 35-50°C for 60-75h to obtain a diaphragm composite material.

[0050] Among them, the preparation method of the aluminum-coated film layer is: using PET film as a substrate, directly through a vacuum coating machine, metal aluminum is evaporated onto the surface of the substrate, thereby forming a metal aluminum layer on the surface of the PET film, and then obtaining an aluminum-coated film layer. The metal aluminum here is only evaporated onto the surface of one side of the PET film, rather than evaporating metal aluminum on both sides of the PET film. In this way, on the one hand, the metal aluminum layer can provide certain damping performance and electromagnetic shielding performance for the diaphragm composite layer, and on the other hand, the setting of the single-sided metal aluminum layer can also save process and consumables; and the setting of the PET film can enhance the strength and heat resistance of the diaphragm composite layer.

[0051] In this embodiment, in step S3, the plasma light speed voltage is 1200-1450 KV, and the irradiation time is 2-5 s.

[0052] In this embodiment, the specific steps for preparing the silicon oxide-silicon nitride composite aerogel in step S2 include:

[0053] 1) The following materials, by mass, are mixed and stirred thoroughly with 1 part of TEOS, (2.5-4) parts of anhydrous ethanol and (2.5-4) parts of water, and the pH value is adjusted to 4 with dilute hydrochloric acid to form sol A;

[0054] 2) adjusting the pH value of sol A to 7 with ammonia water, adding 1 to 1.5 parts by mass of silicon nitride under stirring, and standing at room temperature to form gel B; wherein the average particle size of the silicon nitride is 30 to 50 nm;

[0055] 3) aging gel B at room temperature for 24 h, then immersing gel B in anhydrous ethanol at room temperature and continuing aging for 48 h;

[0056] 4) The aged gel B was immersed in a n-hexane solution containing 10% trimethylsilane for 6 hours to perform a hydrophobic treatment to make the surface more corrosion-resistant;

[0057] The n-hexane solution may also be a n-hexane solution containing 10% trimethylchlorosilane, a n-hexane solution containing 10% long-chain methylsilane, or a n-hexane solution containing 10% methylfluorosilane;

[0058] 5) Drying the gel B treated in step S2.4 at 80-100° C. under normal pressure; treating the dried gel B in a furnace at 450-500° C. for 4-6 hours, and crushing it to obtain a silicon oxide-silicon nitride composite aerogel.

[0059] Example 1

[0060] A diaphragm composite material, comprising a PEN film layer 1, an aluminized film layer 3, an aerogel layer 4, and an elastic adhesive layer 2 arranged between the PEN film layer and the aluminized film layer 3 for bonding the PEN film layer 1 and the aluminized film layer 3, wherein the elastic adhesive layer 2 is made of a thermoplastic elastomer, specifically mainly made of a polyacrylate elastomer or a polyurethane elastomer, and the thickness of the elastic adhesive layer 2 is 12 to 65 μm. The setting of the elastic adhesive layer 2 can not only well bond the PEN film layer 1 and the aluminized film layer 3, but also make the material have a certain toughness, thereby increasing the durability of the product; the aluminized film layer 3 comprises The PET film 31 and the metal aluminum layer 32 vapor-deposited on the surface of the PET film 31, the setting of the metal aluminum layer 32 improves the damping performance and electromagnetic shielding performance of the diaphragm composite layer, and the setting of the PET film 31 increases the strength of the composite film and has better heat resistance; the PEN film layer 1 provides a base material for the diaphragm composite layer, increases the overall rigidity of the diaphragm composite layer, and improves its heat resistance and plasticity. The aerogel layer 4 is coated on the side of the aluminum-plated film layer 3 away from the elastic adhesive layer 2. The setting of the aerogel layer 4 can protect the aluminum-plated film layer and improve its wear resistance and corrosion resistance.

[0061] In this embodiment, the PEN film layer 1 is mainly made of a mixture of polyester PEN, nylon 6 and fiber-type filler.

[0062] In this embodiment, the fiber-type filler is one or more of glass fiber, ceramic fiber, and carbon fiber.

[0063] In this embodiment, the aerogel layer is mainly prepared from silicon oxide-silicon nitride composite aerogel or silicon dioxide-phenolic resin composite aerogel, so that the diaphragm composite layer has better wear resistance and corrosion resistance, making it more durable.

[0064] A method for preparing the above-mentioned diaphragm composite material, the preparation method comprising the following steps:

[0065] S1: Preparation of PEN film layer, the specific preparation steps include:

[0066] S1.1: Dry the material PEN (i.e. polyethylene naphthalate) at 100°C for 2.5h; then weigh the following materials by mass: 70 parts of PEN, 10 parts of nylon 6, 10 parts of fiber-type filler, 1 part of silane coupling agent and 0.5 parts of lubricant; and add the weighed materials into a mixer and mix and stir to form a mixture;

[0067] S1.2: Add ethanol to the mixture and stir, then add it to the extruder for melt blending and extrusion granulation; the mass ratio of ethanol to the mixture is 1:4;

[0068] S1.3: drying the extruded particles in step S1.2 and adding them to an injection molding machine for injection molding to obtain a long-chain branched PEN film layer;

[0069] The silane coupling agent may be KH-550, KH-560 or KH-570;

[0070] Wherein, in step S1.2, the extruder is a twin-screw extruder, the screw speed is 40 rpm, and the temperature from the extruder hopper to the die area is 240°C;

[0071] In step S1.3, the nozzle temperature of the injection molding machine is 250°C and the injection pressure is 65 MPa;

[0072] S2: Preparation of aerogel layer material, the specific preparation steps include: adding 20 parts of propylene oxide, 80 parts of acetic acid, 50 parts of polyethylene glycol 600 and 10 parts of formamide to a high-speed micro-powder mixer and stirring for 5 minutes, and adjusting the solution temperature to 5°C, and then adding 5 parts of silicon oxide-silicon nitride composite aerogel, 20 parts of toluene diisocyanate trimer, and 10 parts of isophorone diisocyanate trimer, and continuing to stir for 5 minutes; then air flow classification, collecting the powder passing through the 8000 mesh filter, which is the aerogel layer material; the speed of the high-speed micro-powder mixer is 800r / min;

[0073] S3: The aerogel layer material powder collected in step S2 is passed through compressed air, filtered, and dried, and then enters a high-temperature gasification chamber at 800°C, and a supersonic airflow is formed through a nozzle and injected into the surface of the aluminum-plated side of the aluminum-plated film layer, and the side surface is continuously irradiated with a high-speed plasma light to form an aluminum-plated film layer with an aerogel layer attached to one side;

[0074] S4: The elastic adhesive is evenly coated on the surface of the PEN film layer, and then laminated and pressed with the surface of the aluminum-coated film layer on the side where the aerogel layer is not attached. The laminating roller dimension is 80°C and the pressure is 120 MPa. After laminating, it is aged at 50°C for 60 hours to obtain a diaphragm composite material.

[0075] Among them, the preparation method of the aluminum-coated film layer is: using PET film as a substrate, directly through a vacuum coating machine, metal aluminum is evaporated onto the surface of the substrate, thereby forming a metal aluminum layer on the surface of the PET film, and then obtaining an aluminum-coated film layer. The metal aluminum here is only evaporated onto the surface of one side of the PET film, rather than evaporating metal aluminum on both sides of the PET film. In this way, on the one hand, the metal aluminum layer can provide certain damping performance and electromagnetic shielding performance for the diaphragm composite layer, and on the other hand, the setting of the single-sided metal aluminum layer can also save process and consumables; and the setting of the PET film can enhance the strength and heat resistance of the diaphragm composite layer.

[0076] In this embodiment, the plasma light speed voltage in step S3 is 1450 KV, and the irradiation time is 3 s.

[0077] In this embodiment, the specific steps for preparing the silicon oxide-silicon nitride composite aerogel in step S2 include:

[0078] 1) The following materials are measured by mass: 1 part of TEOS, 4 parts of anhydrous ethanol and 4 parts of water are fully mixed and stirred, and the pH value is adjusted to 4 (within the allowable error range) with dilute hydrochloric acid to react to form sol A;

[0079] 2) adjusting the pH value of sol A to 7 with ammonia water, adding 1.5 parts by mass of silicon nitride under stirring, and standing at room temperature to form gel B; wherein the average particle size of silicon nitride is 50 nm;

[0080] 3) aging gel B at room temperature for 24 h, then immersing gel B in anhydrous ethanol at room temperature and continuing aging for 48 h;

[0081] 4) The aged gel B was immersed in a n-hexane solution containing 10% trimethylsilane for 6 hours to perform a hydrophobic treatment to make the surface more corrosion-resistant;

[0082] The n-hexane solution may also be a n-hexane solution containing 10% trimethylchlorosilane, a n-hexane solution containing 10% long-chain methylsilane, or a n-hexane solution containing 10% methylfluorosilane;

[0083] 5) The gel B treated in step S2.4 is dried at 80° C. under normal pressure; the dried gel B is treated in a 500° C. furnace for 4 hours and crushed to obtain a silicon oxide-silicon nitride composite aerogel.

[0084] Example 2

[0085] This embodiment is basically the same as Embodiment 1, except that the present embodiment provides a method for preparing the diaphragm composite material, and the method comprises the following steps:

[0086] S1: Preparation of PEN film layer, the specific preparation steps include:

[0087] S1.1: Dry the material PEN (i.e. polyethylene naphthalate) at 130°C for 4h; then weigh the following materials by weight: 80 parts of PEN, 15 parts of nylon 6, 15 parts of fiber-type filler, 2 parts of silane coupling agent and 1 part of lubricant; and add the weighed materials into a mixer and mix and stir to form a mixture;

[0088] S1.2: Add ethanol to the mixture and stir, then add it to the extruder for melt blending and extrusion granulation; the mass ratio of ethanol to the mixture is 1:6;

[0089] S1.3: drying the extruded particles in step S1.2 and adding them to an injection molding machine for injection molding to obtain a long-chain branched PEN film layer;

[0090] The silane coupling agent may be KH-550, KH-560 or KH-570;

[0091] Wherein, in step S1.2, the extruder is a twin-screw extruder, the screw speed is 60 rpm, and the temperature from the extruder hopper to the die area is 260°C;

[0092] In step S1.3, the nozzle temperature of the injection molding machine is 270°C and the injection pressure is 75 MPa;

[0093] S2: Preparation of aerogel layer material, the specific preparation steps include: adding 30 parts of propylene oxide, 130 parts of acetic acid, 70 parts of polyethylene glycol 600 and 30 parts of formamide to a high-speed micro-powder mixer and stirring for 10 minutes, and adjusting the solution temperature to 8°C, and then adding 20 parts of silicon oxide-silicon nitride composite aerogel, 30 parts of toluene diisocyanate trimer, and 15 parts of isophorone diisocyanate trimer, and continuing to stir for 10 minutes; then air flow classification, collecting the powder passing through the 8000 mesh filter, which is the aerogel layer material; the speed of the high-speed micro-powder mixer is 1000r / min;

[0094] S3: The aerogel layer material powder collected in step S2 is passed through compressed air, filtered, and dried, and then enters a 1000°C high-temperature gasification chamber, where a supersonic airflow is formed through a nozzle and injected into the surface of the aluminum-plated side of the aluminum-plated film layer, and the side surface is continuously irradiated with a high-speed plasma light to form an aluminum-plated film layer with an aerogel layer attached to one side;

[0095] S4: The elastic adhesive is evenly coated on the surface of the PEN film layer, and then laminated and pressed with the surface of the aluminum-coated film layer on which the aerogel layer is not attached. The laminating roller dimension is 60°C and the pressure is 160MPa. After laminating, it is aged at 35°C for 75 hours to obtain a diaphragm composite material.

[0096] Among them, the preparation method of the aluminum-coated film layer is: using PET film as a substrate, directly through a vacuum coating machine, metal aluminum is evaporated onto the surface of the substrate, thereby forming a metal aluminum layer on the surface of the PET film, and then obtaining an aluminum-coated film layer. The metal aluminum here is only evaporated onto the surface of one side of the PET film, rather than evaporating metal aluminum on both sides of the PET film. In this way, on the one hand, the metal aluminum layer can provide certain damping performance and electromagnetic shielding performance for the diaphragm composite layer, and on the other hand, the setting of the single-sided metal aluminum layer can also save process and consumables; and the setting of the PET film can enhance the strength and heat resistance of the diaphragm composite layer.

[0097] In this embodiment, the plasma light speed voltage in step S3 is 1200 KV, and the irradiation time is 5 s.

[0098] In this embodiment, the specific steps for preparing the silicon oxide-silicon nitride composite aerogel in step S2 include:

[0099] 1) The following materials are mixed by weight: 1 part of TEOS, 2.5 parts of anhydrous ethanol and 2.5 parts of water are thoroughly stirred and the pH value is adjusted to 4 (within the allowable error range) with dilute hydrochloric acid to form sol A;

[0100] 2) adjusting the pH value of sol A to 7 (within the tolerance range) with ammonia water, adding 1 part by mass of silicon nitride under stirring, and standing at room temperature to form gel B; wherein the average particle size of silicon nitride is 30 nm;

[0101] 3) aging gel B at room temperature for 24 h, then immersing gel B in anhydrous ethanol at room temperature and continuing aging for 48 h;

[0102] 4) The aged gel B was immersed in a hexane solution containing 10% trimethylchlorosilane for 6 hours to perform a hydrophobic treatment to make the surface more corrosion-resistant;

[0103] The n-hexane solution may also be a n-hexane solution containing 10% trimethylsilane, a n-hexane solution containing 10% long-chain methylsilane, or a n-hexane solution containing 10% methylfluorosilane;

[0104] 5) Drying the gel B treated in step S2.4 at 100° C. under normal pressure; treating the dried gel B in a furnace at 450° C. for 6 hours, and crushing the gel to obtain a silicon oxide-silicon nitride composite aerogel.

[0105] The above implementation modes are only used to illustrate the present invention, but not to limit the present invention. Ordinary technicians in the relevant technical field can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, all equivalent technical solutions also belong to the scope of the present invention. The patent protection scope of the present invention should be defined by the claims.

Claims

1. A method for preparing a diaphragm composite material, characterized in that: The invention comprises a PEN film layer (1), an aluminized film layer (3), an aerogel layer (4), and an elastic adhesive layer (2) arranged between the PEN film layer and the aluminized film layer (3) for bonding the PEN film layer (1) and the aluminized film layer (3), wherein the aerogel layer (4) is coated on a side of the aluminized film layer (3) away from the elastic adhesive layer (2), and the aluminized film layer (3) comprises a PET film (31) and a metal aluminum layer (32) vapor-deposited on the surface of the PET film (31); The preparation method comprises the following steps: S1: Preparation of PEN film layer, the specific preparation steps include: S1.1: Weigh the following materials by weight: 70-80 parts of polyethylene naphthalate, 10-15 parts of nylon 6, 10-15 parts of fiber-type filler, 1-2 parts of silane coupling agent and 0.5-1 part of lubricant; add the weighed materials into a mixer, mix and stir to form a mixture; S1.2: Add ethanol to the mixture and stir, then add it to the extruder for melt blending and extrusion granulation; the mass ratio of ethanol to the mixture is 1:(4-6); S1.3: drying the extruded particles in step S1.2 and adding them to an injection molding machine for injection molding to obtain a long-chain branched PEN film layer; S2: Preparation of aerogel layer material, the specific preparation steps include: adding 20-30 parts of propylene oxide, 80-130 parts of acetic acid, 50-70 parts of polyethylene glycol 600 and 10-30 parts of formamide to a high-speed micro-powder mixer and stirring for 5-10 minutes, and adjusting the solution temperature to 5-8°C, then adding 5-20 parts of silicon oxide-silicon nitride composite aerogel, 20-30 parts of toluene diisocyanate trimer, and 10-15 parts of isophorone diisocyanate trimer, and continuing to stir for 5-10 minutes; then airflow classification, collecting the powder passing through an 8000 mesh filter, which is the aerogel layer material; the speed of the high-speed micro-powder mixer is 800-1000r / min; S3: The aerogel layer material powder collected in step S2 is passed through compressed air, filtered, and dried, and then enters a high-temperature gasification chamber of 800-1000°C, and a supersonic airflow is formed through a nozzle and injected into the surface of the aluminum-plated side of the aluminum-plated film layer, and the side surface is continuously irradiated with a high-speed plasma light to form an aluminum-plated film layer with an aerogel layer attached to one side; S4: evenly coating the elastic adhesive on the surface of the PEN film layer, and then laminating and pressing the surface of the aluminum-plated film layer on the side where the aerogel layer is not attached, the laminating roller dimension is 60-80°C, the pressure is 120-160MPa, and after laminating, aging at 35-50°C for 60-75h to obtain a diaphragm composite material; The silicon oxide-silicon nitride composite aerogel is prepared by: 1) mixing the following materials by mass: 1 part of TEOS, (2.5-4) parts of anhydrous ethanol and (2.5-4) parts of water, stirring them evenly, and adjusting the pH value to 4 with dilute hydrochloric acid to react and form sol A; 2) adjusting the pH value of sol A to 7 with ammonia water, adding 1 to 1.5 parts by weight of silicon nitride under stirring, and standing at room temperature to form gel B; 3) aging gel B at room temperature for 24 h, then immersing gel B in anhydrous ethanol at room temperature and continuing aging for 48 h; 4) The aged gel B was immersed in a hexane solution containing 10% trimethylsilane for 6 hours for hydrophobic treatment; 5) drying the gel B treated in step S2.4 at 80-100° C. under normal pressure; treating the dried gel B in a muffle furnace at 450-500° C. for 4-6 hours, and crushing the gel to obtain a silicon oxide-silicon nitride composite aerogel.

2. The method for preparing the diaphragm composite material according to claim 1, characterized in that: The fiber-type filler is one or more of glass fiber, ceramic fiber and carbon fiber.

3. The method for preparing the diaphragm composite material according to claim 1, characterized in that: The elastic adhesive layer (2) is mainly made of polyacrylate elastomer or polyurethane elastomer.

4. The method for preparing the diaphragm composite material according to claim 1, characterized in that: In step S3, the plasma light speed voltage is 1200-1450 KV, and the irradiation time is 2-5 s.

5. The method for preparing the diaphragm composite material according to claim 1, characterized in that: The average particle size of silicon nitride in step 2) is 30 to 50 nm.

Citation Information

Patent Citations

  • Preparation method of silica gel vibrating diaphragm and silica gel vibrating diaphragm

    CN106003668A

  • Composite vibration diaphragm and loudspeaker using same

    CN202873041U

  • Diaphragm of loudspeaker of Bluetooth headset and production process

    CN105163244A

  • Wear-resisting and heat-insulation material and preparation method thereof

    CN109049890A

  • Sound generating mechanism's vibrating diaphragm composite bed and sound generating mechanism

    CN206302564U